Toda a nossa vida ao serviço do povo
Peasant, militant couple with child on a field, contemplating the sun; portrait of Hoji-ya-Henda as the sun Poster advertising day of Angolan youth, 14 April. Suggested translation: Our whole lives at people's service PO-0284